PENGARUH PROGRAM LOYALITAS TERHADAP KEPUASAAN PELANGGAN - Tia Hardiyanti; Cludia Ipara Riswardini; Anggit Dyah Kusumastuti (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
This research aims to gather sufficient information about the impact of loyalty programs on customer satisfaction. This research method is a literature review based on several previous studies to answer the effect of loyalty programs on customer satisfaction. The results of this study indicate that loyalty programs have a significant effect on customer satisfaction. This can be seen in the results of previous research articles which show that loyalty programs have an effect on loyalty.